2015
DOI: 10.1007/s11745-015-4033-9
|View full text |Cite
|
Sign up to set email alerts
|

Glyceroglycolipids Affect Uptake of Carotenoids Solubilized in Mixed Micelles by Human Intestinal Caco‐2 Cells

Abstract: We previously reported that phospholipids markedly affected the uptake of carotenoids solubilized in mixed micelles by human intestinal Caco‐2 cells. In the present study, we found that two classes of dietary glyceroglycolipids and the corresponding lysoglyceroglycolipids affected uptake of β‐carotene and lutein by differentiated Caco‐2 cells. The levels of carotenoid uptake from micelles containing digalactosyldiacylglycerol or sulfoquinovosyldiacylglycerol were significantly lower than that from control mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 62 publications
2
25
1
Order By: Relevance
“…This result, together with our previous report 7 on the uptake of β-carotene and lutein, suggests that these lysoGLs enhance the absorption of various carotenoids with different polarities. We previously reported that the integrity of the intercellular barrier formed by cellto-cell/cell-matrix adhesion participated in the mechanism underlying the effect of lyso-lipids on the carotenoid uptake by Caco-2 cells 7 . In brief, DGMG and SQMG would enhance carotenoid uptake by decreasing the intercellular barrier integrity through the removal of cellular cholesterol, and this applies to carotenoids of a wide polarity range.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…This result, together with our previous report 7 on the uptake of β-carotene and lutein, suggests that these lysoGLs enhance the absorption of various carotenoids with different polarities. We previously reported that the integrity of the intercellular barrier formed by cellto-cell/cell-matrix adhesion participated in the mechanism underlying the effect of lyso-lipids on the carotenoid uptake by Caco-2 cells 7 . In brief, DGMG and SQMG would enhance carotenoid uptake by decreasing the intercellular barrier integrity through the removal of cellular cholesterol, and this applies to carotenoids of a wide polarity range.…”
Section: Discussionsupporting
confidence: 84%
“…However, in the present study, there was no association between the amount of residual micellar carotenoid and the uptake. In addition, we previously found that the concentration of micellar carotenoid at the end of the incubation was not an important factor modulating the uptake 7 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations